2022
DOI: 10.1186/s13048-022-01071-4
|View full text |Cite|
|
Sign up to set email alerts
|

Pivotal role of High-Mobility Group Box 2 in ovarian folliculogenesis and fertility

Abstract: Background High-Mobility Group Box 1 (HMGB1) and HMGB2 are chromatin-associated proteins that belong to the HMG protein family, and are involved in the regulation of DNA transcription during cell differentiation, proliferation and regeneration in various tissues. However, the role of HMGB2 in ovarian folliculogenesis is largely unknown. Methods We investigated the functional role of HMGB1 and HMGB2 in ovarian folliculogenesis and fertilization usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…35 Recently, we reported the pivotal role of HMGB2 in male and female reproductive tissues. 68 We also reported the crucial role of HMGB2 in the regulation of hepatocyte proliferation and cellular size during mouse liver regeneration. 9 However, the detailed molecular mechanisms of HMGB2 in regulating liver regeneration remain largely unknown.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…35 Recently, we reported the pivotal role of HMGB2 in male and female reproductive tissues. 68 We also reported the crucial role of HMGB2 in the regulation of hepatocyte proliferation and cellular size during mouse liver regeneration. 9 However, the detailed molecular mechanisms of HMGB2 in regulating liver regeneration remain largely unknown.…”
Section: Introductionmentioning
confidence: 78%
“…Our other recent studies have also confirmed that HMGB2 is important for cell proliferation in mouse liver, testis, and ovary. [6][7][8] In recent studies, HMGB2 has been reported to be a novel adipogenic gene. The expression of HMGB2 induces adipogenesis in mesenchymal stem cells and fat infiltration into skeletal muscles through the HMG-B2-PDGFRα signaling cascade.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following publication of the original article [ 1 ], the authors identified an error in authorgroup. Author name Fidya Fidya should be Fidya.…”
mentioning
confidence: 99%